2010
DOI: 10.1159/000264612
|View full text |Cite
|
Sign up to set email alerts
|

PSA Decrease with Fulvestrant Acetate in a Hormone-Resistant Metastatic Prostate Cancer Patient

Abstract: Background: Androgen-independent prostate cancer (AIPCA) is a difficult disease to treat. Fulvestrant has shown activity inhibiting estrogen receptor dimerization, and the androgen receptor has been shown to stimulate growth in prostate cancer cell lines. Case Report: A 79-year-old metastatic prostate cancer patient with AIPCA was treated with fulvestrant acetate with a loading dose strategy. Without recording any significant side effects, the prostate-specific antigen (PSA) level decreased from 154 ng/ml to 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…While bevacizumab (VEGF-A monoclonal antibody) has been approved by the U.S. Food and Drug Administration in the treatment of glioblastoma, colorectal cancer, renal cell carcinoma, and other cancer types, some small studies have shown promise in reducing vestibular schwannoma tumor size as well as associated symptomatic improvement. [ 111 130 ] Nevertheless, our understanding of the exact biology of this benign tumor is incomplete and thus warrants further research to elucidate the underlying aberrant molecular signaling. Through a better understanding of the altered signaling pathways in pathology, new therapeutic targets can be identified to improve the outcome of patients with neurosurgical pathologies.…”
Section: Aberrant Signaling In Neurovascular Pathologymentioning
confidence: 99%
“…While bevacizumab (VEGF-A monoclonal antibody) has been approved by the U.S. Food and Drug Administration in the treatment of glioblastoma, colorectal cancer, renal cell carcinoma, and other cancer types, some small studies have shown promise in reducing vestibular schwannoma tumor size as well as associated symptomatic improvement. [ 111 130 ] Nevertheless, our understanding of the exact biology of this benign tumor is incomplete and thus warrants further research to elucidate the underlying aberrant molecular signaling. Through a better understanding of the altered signaling pathways in pathology, new therapeutic targets can be identified to improve the outcome of patients with neurosurgical pathologies.…”
Section: Aberrant Signaling In Neurovascular Pathologymentioning
confidence: 99%
“…Moreover, an in vitro study performed using LNCaP PCa cells suggested that fulvestrant could inhibit AR transcripts, decreasing the response to androgens [ 193 ]. Based on these premises, the drug was tested in clinical trials in men affected by androgen-independent PCa, with contrasting results, animating the debate about its real benefits [ 195 , 195 , 217 , 222 , 223 ]. Interestingly, encouraging data came from the combinatorial use of fulvestrant and immunotherapy, although in the context of breast cancer [ 224 , 225 , 226 , 227 ].…”
Section: Molecules Targeting Nuclear Estrogen Receptorsmentioning
confidence: 99%
“…Transduction pathways should probably be considered when testing AR antagonists: their inhibition may restore sensitivity to androgen antagonists. Anothertherapeuticpathwaycouldbeinterestingtoexplore: J.M.GasentBlesaandV.AlberolaCandelreportinthisissue of OnkOlOgie on the case of a metastatic prostate cancer patient successfully treated with fulvestrant [1]. This 79 year-old patient with initially metastatic prostate cancer first received completeandrogenblockade(CAB)andthenhigh-dosebicalutamide because of intolerance to LH-RH agonist.…”
mentioning
confidence: 99%